2012
DOI: 10.1002/etc.1746
|View full text |Cite
|
Sign up to set email alerts
|

How does growth temperature affect cadmium toxicity measured on different life history traits in the soil nematode Caenorhabditis elegans?

Abstract: Environmental factors, in particular temperature, have been shown to affect the toxicity of chemicals. In the present study the authors exposed the nematode Caenorhabditis elegans to five concentrations of Cd (2, 4, 6, 8, and 10 mg Cd/L agar) at four constant temperatures (11, 15, 18, and 21°C) and monitored survival and reproduction on a daily basis. Data were incorporated in a population matrix model to determine the population growth rate (PGR). An additional experiment at 15 and 20°C and 0, 1, 5, and 10 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
2
17
1
Order By: Relevance
“…The present study presents a unique case of increased metal toxicity with decreasing temperature, when assessed in a reproductive assay. To our knowledge, all previous studies on metal toxicity and temperature have shown either the opposite trend of increasing toxicity with increasing temperature or no temperature effect . Most of these studies have assessed toxicity at identical exposure times rather than at similar physiological times, as was done in the present study, which could have affected the results.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The present study presents a unique case of increased metal toxicity with decreasing temperature, when assessed in a reproductive assay. To our knowledge, all previous studies on metal toxicity and temperature have shown either the opposite trend of increasing toxicity with increasing temperature or no temperature effect . Most of these studies have assessed toxicity at identical exposure times rather than at similar physiological times, as was done in the present study, which could have affected the results.…”
Section: Discussionmentioning
confidence: 88%
“…Other studies on the toxicity of Cd using either population growth rate of nematodes as an endpoint or toxicity after the production of 3 clutches of Daphnia magna , however, still showed higher toxicities at high temperatures, similar to studies using identical exposure times. Only the magnitude of the temperature sensitivity of the toxic response varied between the acute identical time studies and chronic studies assessing toxicities at similar physiological states, as discussed by Nørgaard et al . We therefore believe that the decreased toxicity with increasing temperature observed in the enchytraeids in the present study is related to the temperature affecting the balance of uptake and excretion/immobilization processes of the metals or the balance between damage and repair rates differently from how temperature is affecting these balances in nematodes and daphnia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such costs may decrease the energy available for other functional outputs like growth and reproduction, which can ultimately lead to reduced population growth and survival (Calow & Sibly, 1990). For this reason, quantification of individual life-cycle traits has become a useful tool to assess the risk of anthropogenic pollutants on ecosystems (Kammenga et al, 1996;Nørhave et al, 2012;Jager et al, 2014). Individual growth, reproduction and survival have been the most commonly used parameters (Hansen et al, 1999;Roh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%